Le devoir d'équité procédurale et le contrôle judiciaire ou quasi judiciaire de la procédure administrative - Garant, Patrice (Les Cahiers de droit, 1982)
The doctrine of « procedural fairness » is widening its scope of application to all kinds of administrative decisions. « Procedure » must, as a notion, therefore be clearly defined. The definitions given by the authors or by case-law make it difficult to distinguish between « procedure » and « merits ». The jurisprudence of the Commission de la Fonction publique du Québec, an appeal Tribunal under the Quebec Civil Service Act, is quite relevant since section 77 of the Act gives to the Commission jurisdiction to hear appeals when « the verification procedure of eligibility of candidates or the selection procedure was irregular or illegal ». The Commission, as a specialised expert appeal Tribunal, has adopted a very liberal approach of the concept of procedure. From that experience one may question the diserability of having the ordinary Courts of Justice control of the fairness of administrative procedure. If so, which of an Administrative Tribunal or a Superior Court is the appropriate forum to deal with procedural deficiencies within the administrative process? Up to now, Administrative Tribunals have done well in that field.